Distribution and Population Density of Common Myna (Acridolheres tristis) in UNIMAS Campus, Kota Samarahan, Sarawak - Chieng, Lina Lin Na (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The research project was carried out to investigate the distribution and population density of common myna (Acridotheres tristis) in Universiti Malaysia Sarawak (UNIMAS) campus. The common mynas were observed and studied for a period of six months from November 2014 to April 2015 using line transect method. From the study initiated, a total of 276 common mynas were recorded from 16 road transects done in both East and West of UNIMAS campus. The results showed that the common myna was distributed abundantly throughout the campus and the density of common myna was estimated at 2.42 individuals per hectare. The results also showed that the distribution and density of the common mynas are primarily linked to areas with high human population and food resources. This research has contributed useful information and knowledge for distribution and density of the common myna in a campus environment.